Psychosocial interventions in schizophrenia: a survey of clinical training and clinicians' opinions in India. Issue 1 (2nd January 2018) - Kumar, Devvarta
Abstract: Psychosocial interventions play an important role in improving outcomes for people diagnosed with schizophrenia. However, in lower and middle-income countries (LAMIC), these interventions are often neglected. It is important to understand the reasons for such neglect, and the opinion/views of mental health professionals working in LAMIC can shed significant light on this issue. With this in mind, the present study aimed at surveying the opinion of mental health professionals in India (a LAMIC) regarding four commonly used psychosocial interventions in schizophrenia (Psychoeducation, Cognitive Remediation, Cognitive Behavior Therapy for psychoses, and Social Skills Training) and their level of training in these interventions. A total of 192 mental health professionals were contacted, out of which 42 (22%) completed the survey. The findings indicate that clinicians perceive the importance of psychosocial interventions for psychosis; however, limited resources and inadequate training are major stumbling blocks in using these interventions. The findings have been discussed in light of their implications and the required steps to overcome the hindrances so that most patients benefit from these interventions.